Antimicrobial efficacy of photodynamic therapy against streptococcus mutans bioflim on orthodontic brackets an in vitro study /Maria Angelica B. Barrameda ; thesis - Barrameda, Maria Angelica B.
Introduction: Orthodontic brackets predispose accumulation of dental biofilm causing caries and gingivitis. Mechanical removal of plaque serves as the primary treatment. As adjunct, Chlorhexidine is used but has side-effects like tooth staining and bacterial resistance due to long term use. This study aimed to test the efficacy of another treatment modality to reduce the number of S. mutans in dental biofilm on orthodontic brackets, the Photodynamic Therapy. This involves a photosensitizer activated but light with a specific wavelength producing reactive oxygen species, which kill the bacteria.